An Influence of Organizational Culture, Motivation and Work Discipline on Performance of Employees at the Center For Forest Area Construction, Region I, Medan - Arpika Sari; Rindi Andika; Hasrul Azwar Hasibuan (Britain International for Academic Research (BIAR) Publisher, 2022)
This study was conducted to explain the partial or simultaneous influence of organizational culture, motivation, and work discipline variables on employee performance at the Center for Stabilization of Forest Areas Region I Medan. The total population used was 57 respondents consisting of employees who work at the Forest Area Stabilization Center for Region I Medan, which were taken using a questionnaire that was used as a data collection method in this study. and uses multiple linear regression analysis. The results of the analysis show that there is a simultaneous significant influence between the three variables and a partially significant influence between organizational culture, motivation, and work discipline variables on employee performance at the Forest Area Stabilization Center Region I Medan.